The transmission of bank credit conditions to firms-evidence from linked surveys - Annalisa Ferrando; Sarah Holton; Conor Parle (European Central Bank (ECB), 2024)
Using a novel dataset linking firm level data from the Survey on Access to Finance of Enterprises (SAFE) and bank level data from the Bank Lending Survey (BLS), we explore how changes in credit standards pass through to firms at a granular level. We find that tighter credit standards decrease loan availability reported by firms, increase the likelihood they report access to finance as the worst problem and decrease their investment. After controlling for country-sector-time fixed effects that capture cyclical macroeconomic conditions, effects only remain for firms that need finance. Moreover, we find that a more diversified funding base insulates firms from the negative impacts of tighter credit standards on availability of bank loans and access to finance, although there is little evidence of such an effect for investment. Effects are asymmetric, with stronger impacts recorded for a tightening than an easing. Our results underscore the importance of demand conditions when interpreting the credit conditions and we thus propose a new indicator of demand adjusted credit standards at a euro area level, which can be used to analyse broader credit dynamics.
Keywords: D22; E22; E52; 330; Finance; credit conditions; surveys; firm-bank relationships